Representasi Kesetaraan Gender dalam Reinterpretasi Tokoh Srikandi pada Media Novel Ilustrasi - Margaretha Gunawan; Dewi Isma Aryani; Miki Tjandra (Yayasan Lentera Avanya Nagari, 2026)
This study aims to analyze the representation of gender equality through the reinterpretation of the Srikandi character in an illustrated novel as an effort to reconstruct the meaning of women in a contemporary cultural context. The study uses a Design-Based Research (DBR) approach with qualitative methods supported by descriptive quantitative data. Data were collected through interviews with cultural experts, literature reviews, and questionnaires with 120 respondents aged 11–24 years. The results show that the Srikandi character is represented as an independent, courageous, and agency-based female figure, thus being able to deconstruct traditional gender stereotypes. This reinterpretation also presents the relevance of local cultural values ​​in the modern discourse of gender equality. The questionnaire findings indicate that the majority of respondents are interested in strong female characters and recognize the importance of gender equality issues, although their understanding of cultural symbols is still limited. Illustrated novels as a visual medium have proven to have the potential to be an effective agent of value socialization through an immersive narrative and visual approach. This research contributes to the development of visual communication design as a social practice that is not only aesthetically oriented but also plays a role in shaping community perspectives on gender issues based on local culture. Penelitian ini bertujuan untuk menganalisis representasi kesetaraan gender melalui reinterpretasi tokoh Srikandi dalam media novel ilustrasi sebagai upaya konstruksi ulang makna perempuan dalam konteks budaya kontemporer. Penelitian menggunakan pendekatan Design-Based Research (DBR) dengan metode kualitatif yang didukung data kuantitatif deskriptif. Data dikumpulkan melalui wawancara dengan ahli budaya, kajian literatur, serta kuesioner terhadap 120 responden berusia 11–24 tahun. Hasil penelitian menunjukkan bahwa tokoh Srikandi direpresentasikan sebagai figur perempuan yang mandiri, berani, dan memiliki agensi, sehingga mampu mendekonstruksi stereotip gender tradisional. Reinterpretasi ini juga menghadirkan relevansi nilai budaya lokal dalam wacana kesetaraan gender modern. Temuan kuesioner menunjukkan bahwa mayoritas responden memiliki ketertarikan terhadap karakter perempuan yang kuat dan menyadari pentingnya isu kesetaraan gender, meskipun pemahaman terhadap simbol budaya masih terbatas. Novel ilustrasi sebagai media visual terbukti memiliki potensi sebagai agen sosialisasi nilai yang efektif melalui pendekatan naratif dan visual yang imersif. Penelitian ini berkontribusi pada pengembangan desain komunikasi visual sebagai praktik sosial yang tidak hanya berorientasi estetika, tetapi juga berperan dalam membentuk perspektif masyarakat terhadap isu gender berbasis budaya lokal.